The approximation of the solution of heat conduction problem in circular plate with concentrated initial heat - Akhmedov, Abdulkasim; Salleh, Zuki; Rakhimov, Abdumalik (2022)
Many problems of the engineering sciences can be solved using the modern methods of equations of mathematical physics, particularly elliptic differential equations play essential role in solving heat and mass transfer problems in engineering processes. In this paper, a numerical approximation of the solution of heat conduction problem in circular plate with initial concentrated heat is constructed by using the Riesz means of the spectral decompositions. Solution of heat transfer problems are subjected to the distributional boundary conditions and initial conditions.